The cerebellum and anxiety - Chin, Pei Wern; Augustine, George J. (Frontiers in Cellular Neuroscience, 2023)
Although the cerebellum is traditionally known for its role in motor functions, recent evidence points toward the additional involvement of the cerebellum in an array of non-motor functions. One such non-motor function is anxiety behavior: a series of recent studies now implicate the cerebellum in anxiety. Here, we review evidence regarding the possible role of the cerebellum in anxiety – ranging from clinical studies to experimental manipulation of neural activity – that collectively points toward a role for the cerebellum, and possibly a specific topographical locus within the cerebellum, as one of the orchestrators of anxiety responses.